Cost Driver sebagai Penentu Akurasi Biaya dalam Activity Based Costing: Tinjauan Literatur Sistematis - Suci Aulia; Luffi Lestari; Gita Deprianti; Nabilah Amalia Zahra; Rifani Akbar Sulbahri (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Cost drivers play a central role in Activity-Based Costing (ABC) as they determine how accurately costs are traced and allocated to products or services. This study aims to examine the role of cost drivers as a determinant of cost accuracy in the implementation of ABC. Using a qualitative approach through a Systematic Literature Review, this study reviews prior empirical, conceptual, and bibliometric research that both supports and critiques the application of cost drivers within ABC systems. The results indicate that while ABC has been shown to improve cost accuracy and provide more relevant information for managerial decision-making across manufacturing and service industries, its effectiveness is not without limitations. Several studies reveal that the continued reliance on volume-based cost drivers, limited data quality, and insufficient alignment between activities and cost drivers may reduce the potential benefits of ABC. In addition, contextual factors such as organizational complexity, information system capability, regulatory constraints, and management commitment are frequently cited as key causes of suboptimal ABC implementation. This study concludes that although cost drivers can significantly enhance cost accuracy within ABC, their success depends heavily on the organization’s ability to design and adapt cost drivers to its specific operational conditions and strategic needs.